A systematic study of physical properties of La substituted Sr3Co2Fe24O41 Z-hexaferrites. Issue 3 (1st February 2023) - Singh, Sukhbir; Khichi, Pardeep; Dahiya, Sajjan; Punia, Rajesh; Maan, A.S.; Tripathi, Rahul; Ohlan, Anil
Abstract: The impact of La substitution has been explored systematically in the present work, it covers a rough scan of the range of solubility of Lanthanum in the Sr3 Co2 Fe24 O41 (SCFO) structure. The La substituted Z-type hexaferrites Sr3-x Lax Co2 Fe24 O41, with x = 0.00, 0.15, 0.30, and 0.45, have been prepared via solid-state reaction route and named as SCFO, SLCFO5, SLCFO10 and SLCFO15 respectively. The structure and particle morphology of the samples have been investigated via variety of structural characterization methods like X-ray diffraction (XRD), Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM). A substantial change in structural properties beyond x ≥ 0.45 suggests that their exists a limit of Lanthanum solubility in the Sr3-x Lax Co2 Fe24 O41 which is x = 0.45. The dielectric properties (ε′ & ε′′) of SCFO, SLCFO5, SLCFO10 and SLCFO15 were examined by varying temperature from 313 to 613 K in the frequency range of 500 Hz to 10 MHz. The dielectric responses of all the samples are frequency-dependent and thermally stimulated, with relaxation-type dielectric behavior. From M-H loops, it has been observed that with increasing La substitution, the saturation magnetization value reduces from 63.85 to 59.17 emu/g, whereas coercivity increases from 109.74 to 450.51 oersted, indicating an increase in magnetic hardness. The saturation magnetization (Ms ) and Magneto crystalline anisotropy constant (K1 ) were calculated by fitting the experimental data. A weak signature of magneto-electric coupling is observed by employing an indirect method in the SCFO sample.